Evaluation of the Intraoperative and Postoperative Complications of Orthognathic Surgery - Fatih Mehmet Coşkunses; Hatice Hoşgör; Deniz Akın Ankarali; Sadi Memiş; Berkay Tokuç (Atatürk University, 2024)
Objective: The aim of this study was to evaluate the incidence of preoperative and postoperative complications in patients undergoing orthognathic surgery. Methods: The clinical records and radiographs of 112 patients who undergone orthognathic surgery between 2014 and 2021 were retrospectively analyzed. Patients' demographics, follow-up period, type of malocclusion and operation were recorded. All surgical complications were evaluated into two groups as intraoperative or postoperative complications. Results: The mean age of 112 patients (69 female, 43 male) was 24.4 ± 5.5 (ranging from 16 to 47). The most frequent intraoperative complication was the bad split (5 cases, 4.5%), followed by severe hemorrhage due to rupture of facial artery (1 case, 0.9%), dissection of inferior alveolar nerve (1 case, 0.9%), and dental damage (1 case, 0.9%). The most common postoperative complication was the neurosensorial deficit (29 cases, 25.9%), followed by infection (6 cases, 5.4%), extraoral scar formation (5 cases, 4.5%), fracture of fixation material (2 cases, 1.8%), maxillary non-union (2 cases, 1.8%), postoperative nasal hemorrhage (1 case, 0.9%), and failure of fixation material (1 case, 0.9%). There were no fatal complications. Conclusion: Although the wide range of complications related to orthognathic surgery is reported both in our study and the literature, the frequency of these appears to be uncommon. However, in order to manage the complications of the operation properly, through knowledge and experience are essential. Keywords: Complication, Le Fort I osteotomy, Orthognathic surgery, Sagittal split osteotomy Ortognatik Cerrahi Operasyonu Sırasında ve Sonrasında Gelişen Komplikasyonların Değerlendirilmesi ÖZ Amaç: Bu çalışmanın amacı, ortognatik cerrahi uygulanan hastalarda operasyon sırasında ve sonrasında ortaya çıkan komplikasyonların insidansını değerlendirmektir. Yöntemler: 2014-2021 yılları arasında ortognatik cerrahi operasyonu uygulanan 112 hastanın klinik kayıtları ve radyografileri retrospektif olarak incelendi. Hastaların demografik verileri, takip süresi, maloklüzyon ve operasyon tipi kaydedildi. Tüm cerrahi komplikasyonlar, operasyon sırasında ve sonrasında olmak üzere iki grupta incelenerek değerlendirildi. Bulgular: 112 hastanın (69 kadın, 43 erkek) ortalama yaşı 24,4 ± 5,5 (16-47 arasında) idi. Operasyon sırasında en sık görülen komplikasyon kötü kırık oluşumuydu (5 vaka, %4,5) ve bunu fasiyal arter rüptürüne bağlı olarak görülen şiddetli kanama (1 vaka, %0,9), inferior alveolar sinir diseksiyonu (1 vaka, %0,9) ve dental hasar (1 vaka, %0,9) takip etti. Operasyon sonrasında en sık karşılaşılan komplikasyon ise nörosensoriyel bozukluktu (29 vaka, %25,9) ve bunu enfeksiyon gelişimi (6 vaka, %5,4), ekstraoral skar oluşumu (5 vaka, %4,5), fiksasyon materyalinin fraktürü (2 vaka, %1,8), maksillada osteotomi hattının kemikleşmemesi (2 vaka, %1,8), postoperatif nazal hemoraji (1 vaka, %0,9) ve fiksasyon materyalinin kaybı (1 vaka, %0,9) izledi. Hiçbir hastada hayatı tehdit edici bir komplikasyon ile karşılaşılmadı. Sonuç: Bu çalışmada ve literatürde ortognatik cerrahi ile ilişkili olarak çeşitli komplikasyonlar bildirilse de, bu komplikasyonların görülme sıklığı azdır. Ancak, operasyonda ortaya çıkabilecek komplikasyonların uygun bir şekilde yönetilebilmesi için yeterli bilgi ve deneyime sahip olmak büyük önem taşımaktadır. Anahtar Kelimeler : Le Fort I osteotomisi, Komplikasyon, Ortognatik cerrahi, Sagittal split osteotomy